Penanaman Pendidikan Karakter Kepada Siswa Melalui Program Kurangi Sampah Sekolah Kita “Kurasaki” - Muhammad Dafa Dafiatur Rizqi; Pedro Yehezkiel; Reza Mauldy Raharja (Jurnal Insan Pendidikan dan Sosial Humaniora, 2024)
This research aims to investigate the effect of instilling character education through our school's waste reduction program "kurasaki" and what impact it had on students before and after this program was implemented. The research method used was a qualitative method and data collection was carried out through face-to-face interviews with students and teachers. We chose the location at SMPN 3 Cisoka, Tangerang Banten Regency because the school implements the Irakaki program which can change the character of students to be disciplined, empathetic and caring for the surrounding environment.